Access to higher education among the paudibhuyan tribe in Barkote block, Deogarh District in Odisha: A sociological study (International Journal of Engineering and Computer Science, 2016)
The name of the proposal topic is “Access to higher education among the paudibhuyan tribe in Barkote block, Deogarh District in Odisha: A sociological study”.           Not long ago the idea of tribe, region, and nation conveyed a single complex whole and thus, each could be comprehended if studied along with the others; each term simultaneously incorporated social, geographical and political dimensions. Hence even analytically these were hardly distinguishable. This merely meant that a given socio-cultural collectivity or closely related socio-ethnic categories occupied an ecological territory and had a kind of political structure to manage the system as well as interactions with outsiders, or the “others “. But like all concepts and terms ,they too had to adjust newer political and ideological exigencies .Small wonder the terms currently used are often in comprehensible.         Tribal society is changing. Many sociologist are studies this changing form of tribal society .the change of tribal society is analysis on the basis of the continuum studies in the different countries in this world, among them one of the sociologist studies this changes or development of the tribal society is Robert Redfield Brown and he developed a series of studies on Mexico village, “Rural-Urban-Continuum”.According to 2011 census report Odisha literacy rate 74.45% and paudibhuyan tribal people literacy rate is 19.24%. Around 30% of schools in these   remote areas villages have no teachers or either one teacher are there. More than 75% of paudibhuyan villages are not connected to a road. All 36 paudibhuyn villages are located in   remote forested and hilly areas. Paudibhuyan depends on forest and forest product, eating different fruits, tubers, leaves and seasonal foods like mushrooms, jackfruits, mangoes, bamboo roots etc. They also grow crops like millets, pulses and some paddy if the rainfall is good and timely. Traditionally practitioners of shifting cultivation, most of them have now settled down in permanent habitat. However, the lack of irrigation, uncertain rainfalls and depleting forest and natural resources have resulted in acute shortage of food in the last few years. As a result large number of women and more than 70% children in the villages are malnourished.